Analisis Keterlaksanaan Standar Proses Kurikulum 2013 Di SMA Se-Kabupaten Kepulauan Anambas - Ardian; Nevrita; Nurul Asikin (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2019)
ABSTRACT: The purpose of this study is to describe the implementation of the 2013 curriculum process standards in high schools throughout the Anambas Islands District. This study uses a quantitative approach with descriptive type of research. The population of this study were all 7 biology teachers in the Anambas Islands High School in the total of 7 people, with a study sample of 4 biology teachers taken with Purposive Sampling techniques taking into account the desired data needs. Techniques and instruments for collecting data through questionnaires, observation and documentation. Questionnaire instruments are used to determine the implementation of process standards. Observation is used for knowing the level of implementation of classroom learning and documentation used to determine learning preparation. Based on the analysis of the data that has been obtained, the implementation of the standard process in learning planning obtained an average percentage of 81.83%. In the implementation of learning, the percentage of the average percentage was 75.18% while the results of the learning observations in the class obtained an average percentage of 75.68%. Then the assessment of learning obtained an average percentage of 72.32%. The conclusion in this study is that the implementation of the 2013 curriculum process standards conducted by biology teachers has been classified as good in its implementation. ABSTRAK: Tujuan penelitian ini untuk mendeskripsikan keterlaksanaan standar proses kurikulum 2013 di SMA se-Kabupaten Kepulauan Anambas. Penelitian ini merupakan penelitian yang menggunakan pendekatan kuantitatif dengan jenis penelitian deskriftif. Populasi penelitian ini adalah seluruh guru biologi di SMA Negeri se-Kabupaten Kepulauan Anambas yang berjumlah 7 orang, dengan sampel penelitian 4 orang guru biologi yang diambil dengan teknik Purposive Sampling.dengan pertimbangan kebutuhan data yang diinginkan. Teknik dan instrumen pengumpulan data melalui kuesioner, observasi dan dokumentasi. Intrumen kuesioner digunakan untuk mengetahui keterlaksanaan standar proses. Observasi digunakan untuk mengetahui tingkat pelaksanaan pembelajaran di kelas dan dokumentasi digunakan untuk mengetahui persiapan pembelajaran. Berdasarkan analisis data yang telah didapatkan, keterlaksanaan standar proses pada perencanaan pembelajaran didapatkan rata-rata persentase 81,83%. Pada pelaksanaan pembelajaran didapatkan persentase rata-rata persentase 75,18% sedangkan pada hasil observasi pembelajaran di kelas didapatkan persentase rata-rata 75,68%. Kemudian pada penilaian pembelajaran didapatkan persentase rata-rata 72,32%. Kesimpulan dalam penelitian ini bahwa keterlasanaan standar proses kurikulum 2013 yang dilakukan oleh guru biolgi sudah tergolong baik dalam pelaksanaannya.